Case Report: Long-Term Treatment and Follow-Up of Kleefstra Syndrome-2 - Wu, Dandan; Li, Rong (Frontiers in Pediatrics, 2022)
Background Mutations in the KMT2C gene can cause Kleefstra syndrome-2 (KLEFS2). Case In this study, we analyzed the clinical, genetic testing, and 10-year follow-up data of a child with KLEFS2 treated at the Child Healthcare Department, Children's Hospital of Nanjing Medical University, Nanjing. The case of KLEFS2 presented feeding difficulty and developmental delay, both intervened by nutritional support and family rehabilitation. Obvious attention deficit hyperactivity disorder (ADHD) occurred in preschool and school-age children and was managed by behavioral and pharmaceutical interventions. Conclusion Features of KLEFS2 include feeding difficulty and developmental delays in an early age, as well as ADHD in preschool and school age. Satisfactory outcomes are not achieved in early nutritional support for correcting malnutrition and pharmaceutical intervention for relieving ADHD, but both measures can counter developmental delay.